Analisis Efisiensi Usahatani Kedelai Studi Kasus pada Kabupaten Lampung Timur, Provinsi Lampung - Afriani, Ismalia; Oktaviandi, David; Berliana, Dayang; Supriyadi, Jailan (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
Almost the entire planting of soybean commodity on Sumatra island has decreased. Mostly due to the low soybean productivity so that soybean farming is less attractive and encourages many farmers to switch to other commodities such as corn, peanuts and cassava. The low productivity of soybean is also due to limited capital to buy production facilities in the form of seeds, fertilizers and pesticides while the price of production facilities which from year to year tend to increase, especially the price of artificial fertilizers and pesticidesÂ Besides, the price of soybean during the harvest time is not stabilized and often less profitable farmers. This study aims to measure the level of economic efficiency that includes technical efficiency and allocative efficiency (price) in soybean farming in East Lampung, so it is expected to know the influence of the number of inputs used in soybean farming on the resulting output. Analytical methods used technical efficiency analysis using Data Envelopment Analysis (DEA) application, cost / allocative efficiency analysis and economic efficiency analysis. The results showed that the average technical efficiency of soybean farming system = 1 means that in general the soybean farming has reached the level of technical efficiency. The average value of the allocative efficiency of 1,4 means that on average the allocative efficiency level of oybean farming has not been achieved. The value of economic efficiency 1.4 is greater than 1. This means that maximum economic efficiency in East Lampung regency has not been achieved, therefore the use of production factors need to be added in order to achieve efficiency condition.